Predicting Air Flow in Calendered Paper Sheets from μ-CT Data: Combining Physics with Morphology - Phillip Gräfensteiner; Andoni Rodriguez; Peter Leitl; Ekaterina Baikova; Maximilian Fuchs; Eduardo Machado Charry; Ulrich Hirn; André Hilger; Ingo Manke; Robert Schennach; Matthias Neumann; Volker Schmidt; et al. (Transport in Porous Media, 2026)
Predicting the macroscopic properties of thin fiber-based porous materials from their microscopic morphology remains challenging because of the structural heterogeneity of these materials. In this study, computational fluid dynamics simulations were performed to compute volume air flow based on tomographic image data of uncompressed and compressed paper sheets. To reduce computational demands, a pore network model was employed, allowing volume air flow to be approximated with less computational effort. To improve prediction accuracy, geometric descriptors of the pore space, such as porosity, surface area, median pore radius, and geodesic tortuosity, were combined with predictions of the pore network model. This integrated approach significantly improves the predictive power of the pore network model and indicates which aspects of the pore space morphology are not accurately represented within the pore network model. In particular, we illustrate that a high correlation among descriptors does not necessarily imply redundancy in a combined prediction.

Per- and Polyfluoroalkyl Substance (PFAS) Levels in Human Plasma Samples Originating from Four Regions with Known Environmental Pollution Compared To Four Nearby Control Regions in Bavaria - Bettina Aschenbrenner; Mandy Wöckner; Veronika Fuchs; Lorena M. Cursino Hron; Caroline Herr; Wolfgang Schober; Dennis Nowak; Matthias Graw; Stefanie Heinze; Wolfgang Völkel (Exposure and Health, 2026)

A single specific and actionable swap recommendation can lead to substantial reductions in households’ dietary carbon footprints - Kevin O'Sullivan; Verena Tiefenbeck; Matthias Stucki; Sebastian Bradford; Klaus Ludwig Fuchs; Silvan Wanner; Elgar Fleisch (Journal of Cleaner Production, 2025)

The Local Turn in a Global Sea: Identifying Sustainability Trade‐Offs in Regionalized Marine Aquaculture Systems - Gesche Krause; Ramón Filgueira; Nesar Ahmed; Karen A. Alexander; Furqan Asif; Lucia Fanning; Sebastian C. A. Ferse; Nike Fuchs; Jon Grant; Jordi Guillen; Christina Hörterer; Teresa R. Johnson; et al. (Reviews in Aquaculture, 2025)
Marine aquaculture, like the broader seafood industry, relies heavily on international trade and global supply chains for both production and sales. Recent global disruptions, including the COVID‐19 pandemic, the Russian invasion of Ukraine, the conflicts in the Middle East, and trade tensions, have exposed the social and economic vulnerabilities inherent in a globalized production system. In response, these events have sparked growing interest in transitioning to localized and regional supply chain models. Calls to “buy national” and support domestic economies highlight this trend toward regionalization. This study explores the sustainability implications of regionalizing marine aquaculture by examining the four key segments of the supply chain. These are (1) upstream inputs and resources (2) aquaculture production (3) downstream added value‐processing and (4) distribution–transportation. Potential benefits of regional production models include increased resilience to disruptions, lower transportation‐related carbon emissions, and support for local economies. However, such models may also introduce trade‐offs, including reduced production efficiency, supply and sales limitations, and implications for social, cultural, and governance structures. Our analysis reveals that the sustainability outcomes of regionalization are complex and context‐dependent. It is influenced by the specific characteristics of existing supply chains and the regional contexts in which they operate. While regionalization may offer advantages in certain contexts, it does not guarantee improved sustainability. Thus, it is crucial to critically assess the assumption that regionalization inherently leads to improved sustainability outcomes. Proactive evaluation of these dynamics is essential to develop strategies that maximize benefits while addressing potential trade‐offs.

A Review of Abrupt Permafrost Thaw: Definitions, Usage, and a Proposed Conceptual Framework - Hailey Webb; Matthias Fuchs; Benjamin W. Abbott; Thomas A. Douglas; Clayton D. Elder; Jessica Gilman Ernakovich; Eugenie S. Euskirchen; Mathias Göckede; Guido Grosse; Gustaf Hugelius; Miriam C. Jones; Charles Koven; et al. (Current Climate Change Reports, 2025)
Purpose of Review We review how ‘abrupt thaw’ has been used in published studies, compare these definitions to abrupt processes in other Earth science disciplines, and provide a definitive framework for how abrupt thaw should be used in the context of permafrost science. Recent Findings We address several aspects of permafrost systems necessary for abrupt thaw to occur and propose a framework for classifying permafrost processes as abrupt thaw in the future. Based on a literature review and our collective expertise, we propose that abrupt thaw refers to thaw processes that lead to a substantial persistent environmental change within a few decades. Abrupt thaw typically occurs in ice-rich permafrost but may be initiated in ice-poor permafrost by external factors such as hydrologic change (i.e., increased streamflow, soil moisture fluctuations, altered groundwater recharge) or wildfire. Summary Permafrost thaw alters greenhouse gas emissions, soil and vegetation properties, and hydrologic flow, threatening infrastructure and the cultures and livelihoods of northern communities. The term ‘abrupt thaw’ has emerged in scientific discourse over the past two decades to differentiate processes that rapidly impact large depths of permafrost, such as thermokarst, from more gradual, top-down thaw processes that impact centimeters of near-surface permafrost over years to decades. However, there has been no formal definition for abrupt thaw and its use in the scientific literature has varied considerably. Our standardized definition of abrupt thaw offers a path forward to better understand drivers and patterns of abrupt thaw and its consequences for global greenhouse gas budgets, impacts to infrastructure and land-use, and Arctic policy- and decision-making.

Methane flux from Beringian coastal wetlands for the past 20,000 years - Matthias Fuchs; Miriam C. Jones; Evan J. Gowan; Steve Frolking; Katey Walter Anthony; Guido Grosse; Benjamin M. Jones; Jonathan A. O'Donnell; Laura Brosius; Claire Treat (Quaternary Science Reviews, 2024)

Large inter-annual variation in carbon sink strength of a permanent grassland over 16 years: Impacts of management practices and climate - Iris Feigenwinter; Lukas Hörtnagl; Matthias J. Zeeman; Werner Eugster; Kathrin Fuchs; Lutz Merbold; Nina Buchmann (Agricultural and Forest Meteorology, 2023)

Correction to: The challenge to use multi-temporal InSAR for landslide early warning - Matthias Schlögl; Karlheinz Gutjahr; Sven Fuchs (Natural Hazards, 2022)

The challenge to use multi-temporal InSAR for landslide early warning - Matthias Schlögl; Karlheinz Gutjahr; Sven Fuchs (Natural Hazards, 2022)
Satellite radar interferometry is a powerful tool for measuring displacements of the Earth’s surface. However, we recommend to extend the currently prevailing focus on ex-post analyses and monitoring towards ex-ante early warning applications. Underlying challenges and key requirements are discussed.

Cover Image: Volume 25 Number 3, March 2022 - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)

AVONET: morphological, ecological and geographical data for all birds - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)
Functional traits offer a rich quantitative framework for developing and testing theories in evolutionary biology, ecology and ecosystem science. However, the potential of functional traits to drive theoretical advances and refine models of global change can only be fully realised when species‐level information is complete. Here we present the AVONET dataset containing comprehensive functional trait data for all birds, including six ecological variables, 11 continuous morphological traits, and information on range size and location. Raw morphological measurements are presented from 90,020 individuals of 11,009 extant bird species sampled from 181 countries. These data are also summarised as species averages in three taxonomic formats, allowing integration with a global phylogeny, geographical range maps, IUCN Red List data and the eBird citizen science database. The AVONET dataset provides the most detailed picture of continuous trait variation for any major radiation of organisms, offering a global template for testing hypotheses and exploring the evolutionary origins, structure and functioning of biodiversity.

Seasonal nitrogen fluxes of the Lena River Delta - Tina Sanders; Claudia Fiencke; Matthias Fuchs; Charlotte Haugk; Bennet Juhls; Gesine Mollenhauer; Olga Ogneva; Paul Overduin; Juri Palmtag; Vasily Povazhniy; Jens Strauss; Robyn Tuerena; et al. (Ambio, 2022)
The Arctic is nutrient limited, particularly by nitrogen, and is impacted by anthropogenic global warming which occurs approximately twice as fast compared to the global average. Arctic warming intensifies thawing of permafrost-affected soils releasing their large organic nitrogen reservoir. This organic nitrogen reaches hydrological systems, is remineralized to reactive inorganic nitrogen, and is transported to the Arctic Ocean via large rivers. We estimate the load of nitrogen supplied from terrestrial sources into the Arctic Ocean by sampling in the Lena River and its Delta. We took water samples along one of the major deltaic channels in winter and summer in 2019 and sampling station in the central delta over a one-year cycle. Additionally, we investigate the potential release of reactive nitrogen, including nitrous oxide from soils in the Delta. We found that the Lena transported nitrogen as dissolved organic nitrogen to the coastal Arctic Ocean and that eroded soils are sources of reactive inorganic nitrogen such as ammonium and nitrate. The Lena and the Deltaic region apparently are considerable sources of nitrogen to nearshore coastal zone. The potential higher availability of inorganic nitrogen might be a source to enhance nitrous oxide emissions from terrestrial and aquatic sources to the atmosphere.

Degrading permafrost river catchments and their impact on Arctic Ocean nearshore processes - Paul J. Mann; Jens Strauss; Juri Palmtag; Kelsey Dowdy; Olga Ogneva; Matthias Fuchs; Michael Bedington; Ricardo Torres; Luca Polimene; Paul Overduin; Gesine Mollenhauer; Guido Grosse; et al. (Ambio, 2022)
Arctic warming is causing ancient perennially frozen ground (permafrost) to thaw, resulting in ground collapse, and reshaping of landscapes. This threatens Arctic peoples' infrastructure, cultural sites, and land-based natural resources. Terrestrial permafrost thaw and ongoing intensification of hydrological cycles also enhance the amount and alter the type of organic carbon (OC) delivered from land to Arctic nearshore environments. These changes may affect coastal processes, food web dynamics and marine resources on which many traditional ways of life rely. Here, we examine how future projected increases in runoff and permafrost thaw from two permafrost-dominated Siberian watersheds—the Kolyma and Lena, may alter carbon turnover rates and OC distributions through river networks. We demonstrate that the unique composition of terrestrial permafrost-derived OC can cause significant increases to aquatic carbon degradation rates (20 to 60% faster rates with 1% permafrost OC). We compile results on aquatic OC degradation and examine how strengthening Arctic hydrological cycles may increase the connectivity between terrestrial landscapes and receiving nearshore ecosystems, with potential ramifications for coastal carbon budgets and ecosystem structure. To address the future challenges Arctic coastal communities will face, we argue that it will become essential to consider how nearshore ecosystems will respond to changing coastal inputs and identify how these may affect the resiliency and availability of essential food resources.

A high leukocyte count and administration of hydrocortisone hamper PCR-based diagnostics for bloodstream infections - Silke Huber; Johannes Weinberger; Matthias Pilecky; Ingo Lorenz; Anita Schildberger; Viktoria Weber; Stefan Fuchs; Wilfried Posch; Ludwig Knabl; Reinhard Würzner; Andreas E. Posch; Dorothea Orth-Höller (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Persistence with VKA treatment in newly treated atrial fibrillation patients: an analysis based on a large sample of 38,076 German patients - Thomas Wilke; Antje Groth; Andreas Fuchs; Matthias Pfannkuche; Ulf Maywald (European Journal of Clinical Pharmacology, 2017)

Qualifizierung für „Industrie 4.0“ - Martina Fuchs; Matthias Pilz; Judith Wiemann; Kristina Wiemann (Standort, 2017)

Chlamydial seasonal dynamics and isolation of ‘ C andidatus N eptunochlamydia vexilliferae’ from a T yrrhenian coastal lake - Ilaria Pizzetti; Frederik Schulz; Tomáš Tyml; Bernhard M. Fuchs; Rudolf Amann; Matthias Horn; Stefano Fazi (Environmental Microbiology, 2016)
Summary The C hlamydiae are a phylum of obligate intracellular bacteria comprising important human and animal pathogens, yet their occurrence in the environment, their phylogenetic diversity and their host range has been largely underestimated. We investigated the seasonality of environmental chlamydiae in a Tyrrhenian coastal lake. By catalysed reporter deposition fluorescence in situ hybridization, we quantified the small planktonic cells and detected a peak in the abundance of environmental chlamydiae in early autumn with up to 5.9 × 10 4 cells ml −1 . Super‐resolution microscopy improved the visualization and quantification of these bacteria and enabled the detection of pleomorphic chlamydial cells in their protist host directly in an environmental sample. To isolate environmental chlamydiae together with their host, we applied a high‐throughput limited dilution approach and successfully recovered a V exillifera sp., strain harbouring chlamydiae (93% 16 S r RNA sequence identity to S imkania negevensis ), tentatively named ‘ C andidatus N eptunochlamydia vexilliferae’. Transmission electron microscopy in combination with fluorescence in situ hybridization was used to prove the intracellular location of these bacteria representing the first strain of marine chlamydiae stably maintained alongside with their host in a laboratory culture. Taken together, this study contributes to a better understanding of the distribution and diversity of environmental chlamydiae in previously neglected marine environments.

Screen for alterations of iron related parameters in N-ethyl-N-nitrosourea-treated mice identified mutant lines with increased plasma ferritin levels - Birgit Rathkolb; Martina Klempt; Sibylle Sabrautzki; Dian Michel; Matthias Klaften; Jürgen Laufs; Reinhard Sedlmeier; Wolfgang Hans; Helmut Fuchs; Martina U. Muckenthaler; Marion Horsch; Dean R. Campagna; et al. (BioMetals, 2015)

Erratum to: New mouse models for metabolic bone diseases generated by genome-wide ENU mutagenesis - Sibylle Sabrautzki; Isabel Rubio-Aliaga; Wolfgang Hans; Helmut Fuchs; Birgit Rathkolb; Julia Calzada-Wack; Christian M. Cohrs; Matthias Klaften; Hartwig Seedorf; Sebastian Eck; Ana Benet-Pagès; Jack Favor; et al. (Mammalian Genome, 2014)

CXCR4 antibody treatment suppresses metastatic spread to the lung of intratibial human osteosarcoma xenografts in mice - Patrick Brennecke; Matthias J. E. Arlt; Carmen Campanile; Knut Husmann; Ana Gvozdenovic; Tiziana Apuzzo; Marcus Thelen; Walter Born; Bruno Fuchs (Clinical & Experimental Metastasis, 2014)

New mouse models for metabolic bone diseases generated by genome-wide ENU mutagenesis - Sibylle Sabrautzki; Isabel Rubio-Aliaga; Wolfgang Hans; Helmut Fuchs; Birgit Rathkolb; Julia Calzada-Wack; Christian M. Cohrs; Matthias Klaften; Hartwig Seedorf; Sebastian Eck; Ana Benet-Pagès; Jack Favor; et al. (Mammalian Genome, 2012)

A dietary pattern that is associated with C-peptide and risk of colorectal cancer in women - Teresa T. Fung; Frank B. Hu; Matthias Schulze; Michael Pollak; Tianying Wu; Charles S. Fuchs; Edward Giovannucci (Cancer Causes & Control, 2012)

Einsatz des nofdp IDSS im Rahmen der Konzeption naturverträglicher Hochwasserschutzmaßnahmen an der Mümling - Kaj Lippert; Michael Haase; Thorsten Hens; Monika Thül; Elmar Fuchs; Peter Horchler; Christoph Hübner; Manfred Ostrowski; Stephan Rosenzweig; Matthias Sottong; Axel Winterscheid (WASSERWIRTSCHAFT, 2009)

Storage and mobility of black carbon in permafrost soils of the forest tundra ecotone in Northern Siberia - GEORG GUGGENBERGER; ANDREJ RODIONOV; OLGA SHIBISTOVA; MATTHIAS GRABE; OLEG A. KASANSKY; HANS FUCHS; NATALIA MIKHEYEVA; GALINA ZRAZHEVSKAYA; HEINER FLESSA (Global Change Biology, 2008)
Boreal permafrost soils store large amounts of organic carbon (OC). Parts of this carbon (C) might be black carbon (BC) generated during vegetation fires. Rising temperature and permafrost degradation is expected to have different consequences for OC and BC, because BC is considered to be a refractory subfraction of soil organic matter. To get some insight into stocks, variability, and characteristics of BC in permafrost soils, we estimated the benzene polycarboxylic acid (BPCA) method‐specific composition and storage of BC, i.e. BPCA‐BC, in a 0.44 km 2 ‐sized catchment at the forest tundra ecotone in northern Siberia. Furthermore, we assessed the BPCA‐BC export with the stream draining the catchment. The catchment is composed of various landscape units with south‐southwest (SSW) exposed mineral soils characterized by thick active layer or lacking permafrost, north‐northeast (NNE) faced mineral soils with thin active layer, and permafrost‐affected raised bogs in plateau positions showing in part thermokarst formation. There were indications of vegetation fires at all landscape units. BC was ubiquitous in the catchment soils and BPCA‐BC amounted to 0.6–3.0% of OC. This corresponded to a BC storage of 22–3440 g m −2 . The relative contribution of BPCA‐BC to OC, as well as the absolute stocks of BPCA‐BC were largest in the intact bogs with a shallow active layer followed by mineral soils of the NNE aspects. In both landscape units, a large proportion of BPCA‐BC was stored within the permafrost. In contrast, mineral soils with thick active layer or lacking permafrost and organic soils subjected to thermokarst formation stored less BPCA‐BC. Permafrost is, hence, not only a crucial factor in the storage of OC but also of BC. In the stream water BPCA‐BC amounted on an average to 3.9% of OC, and a yearly export of 0.10 g BPCA‐BC m −2 was calculated, most of it occurring during the period of snow melt with dominance of surface flow. This suggests that BC mobility in dissolved and colloidal phase is an important pathway of BC export from the catchment. Such a transport mechanism may explain the high BC concentrations found in sediments of the Arctic Ocean.

Überprüfung von Abflusskurven an Pegeln mittlerer und kleinerer Flüsse unter Verwendung hydraulischer 2-D-Modelle - Matthias Bleck; Christian Fuchs; Werner Follardt; Ralf-Michael Umlauf (WASSERWIRTSCHAFT, 2007)

The suitability of different DHB isomers as matrices for the MALDI-TOF MS analysis of phospholipids: which isomer for what purpose? - Jürgen Schiller; Rosmarie Süß; Beate Fuchs; Matthias Müller; Marijana Petković; Olaf Zschörnig; Hanka Waschipky (European Biophysics Journal, 2007)

Morphologic and molecular characterization of two novel Krt71 (Krt2-6g) mutations: Krt71 rco12 and Krt71 rco13 - Fabian Runkel; Matthias Klaften; Kerstin Koch; Volker Böhnert; Heinrich Büssow; Helmut Fuchs; Thomas Franz; Martin Hrabé de Angelis (Mammalian Genome, 2006)

Differential induction of enzymes involved in anaerobic metabolism of aromatic compounds in the denitrifying bacterium Thauera aromatica - J. Heider; Matthias Boll; Klaus Breese; Sabine Breinig; Christa Ebenau-Jehle; Ulrich Feil; Nasser Gad'on; Diana Laempe; Birgitta Leuthner; M. El-Said Mohamed; Sabine Schneider; Gerhard Burchhardt; et al. (Archives of Microbiology, 1998)